“Estructuración de un modelo de distribución y comercialización de productos de consumo general, elaborados y producidos por la red de Economía Popular y Solidaria (EPS) de la zona Quitumbe del Distrito Metropolitano de Quito.” - Layedra Molina, Jenny (2012)
With a marketing system and distribution is to help people make the Associative Enterprises and their families toward the overall development, economic, social and environmental sustainability, as the price of products or services allow decent living conditions for producers, consumers get quality products, manufactured under standards of environmental care at a fair price, eliminating the intermediary in a spirit of self-employment lucro.De this way promotes and is provided with a grain of sand to a better quality of life for dozens of families Quitumbe Zone Quito.